Stroke due to Percheron artery occlusion: description of a consecutive case series from Southern Portugal - Reis, Diana (2022)
The artery of Percheron (AOP) is an abnormal variant of the arterial supply of the thalamus. Stroke caused by AOP occlusion is seldom reported. AOP leads to bilateral thalamic and rostral midbrain infarct presenting with unspecific manifestations. There are few descriptions of case series of stroke caused by AOP. We sought to review the clinicoradiological characteristics of AOP infarction from Algarve, Southern Portugal. Eight consecutive cases were retrospectively identified by searching the electronic clinical charts, as well as the stroke Unit database (2015–2020). Sociodemographic (age and gender) and clinicoradiological characteristics (etiological classification, admission severity, manifestations, and short- and long-term prognoses) were retrieved. The corresponding frequency of AOP infarction was 0.17% (95% confidence interval: 0.05–0.28). The mean age was 67.1 (range: 60–80) years. The range of stroke severity evaluated assessed by the National Institute of Health Stroke Scale ranged from 5 to 23 (median ¼ 7.5). None of the patients receive acute ischemic stroke reperfusion treatment. AOP patterns were isolated bilateral paramedian thalamic (n ¼ 2), bilateral paramedian and anterior thalamic (n ¼ 2), and bilateral paramedian thalamic with rostral midbrain (n ¼ 4). Two patients (20%) died on the short term (30 days). At hospital discharge, six patients had functional disability of 2 on the modified Rankin scale. In the follow-up at 6 months, half (n ¼ 3) of the survivors had persistent hypersomnia and two had vascular dementia. Stroke from AOP presents with variable clinical and radiological presentations and patients do not receive alteplase. The shortterm survivor and the long-term functional independency can be compromised after AOS infarct.